MC4R Is Involved in Neuropathic Pain by Regulating JNK Signaling Pathway After Chronic Constriction Injury - Zhao, Yang; Xin, Yan; Chu, Haichen (Frontiers in Neuroscience, 2019)
Background: Neuropathic pain can develop after nerve injury, when deleterious changes occur in injured neurons and glia cells. Melanocortin 4 receptor (MC4R) was involved in the regulation of pain due to its high expressions in brain. Moreover, MC4R could mediate the c-Jun N-terminal kinase (JNK) signaling pathway, but whether the MC4R-regulated JNK signaling pathway participated in neuropathic pain after chronic constriction injury (CCI) is still unclear. Methods: 128 Sprague-Dawley rats were allocated into 4 experiment groups: SHAM group, CCI+NaCl group, CCI+HS group and CCI+SP+HS group. For CCI+NaCl group, the sciatic nerves were ligated. For the SHAM group, an identical manner to the CCI without ligation was performed. For CCI+HS and CCI+SP+HS groups, rats were injected with MC4R inhibitor (HS014) and HS014 plus JNK inhibitor (SP600125) respectively from day 3 to day 14 after CCI. Paw withdrawal latency (PWL) and paw withdrawal threshold (PWT) were used to assess the nociceptive behavior. Elisa was used to detect the levels of inflammatory cytokines. qRT-PCR and Western Blots (WB) were utilized to examine the mRNA and protein expressions of JNK signaling pathway-related genes. Meanwhile, the expression levels of MC4R and p-JNK were further evaluated by IHC and IF experiments. Finally, in order to confirm the in vivo results, astrocytes were isolated and transfected with MC4R-overexpression plasmid. Furthermore, the protein expressions of JNK signaling pathway-related genes were tested by WB. Results:The values of PWL and PWT were significantly increased in CCI+HS group and CCI+SP+HS group as compared with CCI+NaCl group. The increased IL-6, IL-1β and TNF-α secretions in CCI+NaCl group were lowered by HS and SP+HS. MC4R, p-JNK, ATF3 and c-Jun levels were up-regulated with CCI surgery, but down-regulated with HS and SP+HS treatments. Moreover, the IHC and IF results further revealed that MC4R and p-JNK expressions in CCI+NaCl group were remarkably higher than those in HS group and HS+SP group. In vitro data also indicated that HS, SP and SP+HS could down-regulate the expressions of MC4R, p-JNK, ATF3 and c-Jun in M1830 astrocytes. Conclusion: Our findings indicated that MC4R is involved in neuropathic pain by regulating JNK signaling pathway after CCI.